An Analysis of Class 2 Students Beginning Reading Difficulties in Indonesian Language Lesson Content - Tassya Deviani; Deni Setiawan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
Reading is a fundamental skill that underpins the entire learning process and must be mastered by students at an early stage. This study aims to examine the nature of initial reading difficulties among second-grade students, identify contributing factors, and explore effective interventions within the context of Indonesian language learning. Employing a qualitative approach, data were collected through observations, interviews, and documentation. The data analysis followed the Miles and Huberman model, with validity ensured through technical triangulation. The findings reveal a range of reading difficulties experienced by students, including the inability to recognize letters, distinguish between similar-looking letters, differentiate vowels and consonants, fluently decode words, and construct sentences. A significant contributing factor identified is the lack of support and involvement from the family environment, particularly parental attention. To address these challenges, teachers implemented engaging and interactive learning media to create a playful and enjoyable learning atmosphere. The study highlights the importance of teacher initiatives in designing student-centered reading interventions and underscores the need for strong communication between educators and parents to support students facing early reading challenges. These findings have implications for improving early literacy strategies and fostering collaborative efforts between schools and families in addressing learning difficulties.